1968
DOI: 10.1182/blood.v31.5.653.653
|View full text |Cite
|
Sign up to set email alerts
|

Blood Cell Separation in the Dog by Continuous Flow Centrifugation

Abstract: A closed continuous flow centrifuge was used to separate and collect large quantities of buffy coat cells from the dog. One hundred fifty-five separate centrifugations of 2-12 hours duration were performed. Up to 61.0 liters of blood, representing 2.2-52 donor blood volumes, were processed. Buffy coat cells with a preponderance of granulocytes or lymphocytes, were collected while plasma and red blood cells were returned to the donor without change in flow or gravitational field. The mean total number of leukoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
18
0

Year Published

1970
1970
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(18 citation statements)
references
References 15 publications
0
18
0
Order By: Relevance
“…[7][8][9] Development of techniques to both increase peripheral blood mononuclear cell (PBMC) counts using cloned hematopoietic cytokines 10,11 and collect large numbers of these cells via centrifugation using continuous-flow blood separators increased yields. [12][13][14] In dogs, both autologous 15,16 and allogeneic 17 PBMC grafts were able to reconstitute normal hematopoiesis after lethal bone marrow ablation. Freshly isolated PBMC grafts were used to treat dogs in remission for LSA after high-dose total body irradiation, with approximately 25% becoming disease-free long-term survivors.…”
mentioning
confidence: 99%
“…[7][8][9] Development of techniques to both increase peripheral blood mononuclear cell (PBMC) counts using cloned hematopoietic cytokines 10,11 and collect large numbers of these cells via centrifugation using continuous-flow blood separators increased yields. [12][13][14] In dogs, both autologous 15,16 and allogeneic 17 PBMC grafts were able to reconstitute normal hematopoiesis after lethal bone marrow ablation. Freshly isolated PBMC grafts were used to treat dogs in remission for LSA after high-dose total body irradiation, with approximately 25% becoming disease-free long-term survivors.…”
mentioning
confidence: 99%
“…F or more than 5 decades, the dog has served as an excellent random-bred preclinical model for human hematopoietic cell transplantation (HCT). 1,2 Studies in the canine model concerning the impact of histocompatibility barriers on engraftment and graft-versus-host disease (GVHD), 3 in vivo [4][5][6][7][8] and in vitro [9][10][11][12] graft manipulation, peripheral blood mononuclear cell (PBMC) collection, [13][14][15][16][17][18][19] kinetics of immunological reconstitution after bone marrow and PBMC grafting, 20,21 cell dose requirements, [21][22][23][24] efficacy of various pretransplant conditioning regimens [25][26][27][28][29][30][31][32][33][34] and posttransplant immunosuppression protocols, [35][36][37][38][39] treatment of malignant diseases, [40][41][42][43][44][45][46][47][48] and graft-versus-tumor (GVT...…”
mentioning
confidence: 99%
“…15 Since then, various PBMC collection and isolation methods have been adopted for the canine HCT model. 2,11,12,14,[16][17][18][19] Extensive preclinical studies showed that both autologous 10,20,21,53 and allogeneic 3,13 PBMC grafts reconstituted normal hematopoiesis in dogs undergoing otherwise lethal bone marrow ablation. It was also established that 10 times more PBMCs than marrow cells were required to induce regeneration of hematopoietic cell lineages in a timely fashion and assure stable engraftment.…”
mentioning
confidence: 99%
“…The NCI-IBM continuous flow blood cell centrifuge was adapted for use in the dog, based in part on the recent findings of Judson, Jones, Buckner, and associates (Judson et al, 1968;Jones, 1968;Buckner et al, 1968).…”
Section: Methodsmentioning
confidence: 99%